Exploring the New Horizon of AdipoQ in Obesity-Related Alzheimer’s Dementia - Uddin, Md. Sahab; Rahman, Md. Motiar; Sufian, Mohammad Abu; Jeandet, Philippe; Ashraf, Ghulam Md.; Bin-Jumah, May N.; Mousa, Shaker A.; Abdel-Daim, Mohamed M.; Akhtar, Muhammad Furqan; Saleem, Ammara; Amran, Md. Shah (Frontiers in Physiology, 2021)
Alzheimer's disease (AD) is the most common form of dementia, which causes abnormalities in learning, thinking, memory, as well as behavior. Generally, symptoms of AD develop gradually and aggravate over time, and consequently interfere severely with daily activities. Furthermore, obesity is one of the common risk factors for dementia. Dysregulation of adipokine and adipocyte dysfunction are assumed to be accountable for the high risk of obesity in people that develop many related disorders such as AD. Moreover, it has been observed that the dysfunction of adipose is connected with changes in brain metabolism, brain atrophy, cognitive decline, impaired mood, neuroinflammation, impaired insulin signaling, and neuronal dysfunction in people with obesity. Conversely, the pathological mechanisms, as well as the molecular players which are involved in this association, are unclear till now. In this article, we discuss the impact of adiponectin (AdipoQ) on obesity-related Alzheimer’s dementia.